Beauchamp and Childress’ principlism: theoretical reasons of some persistent conceptual issues - Furlan, Enrico (Medicina e Morale, 2024)
Beauchamp and Childress' principlism is probably the most influential model for justifying bioethical judgements at the international level. Despite its widespread adoption and influence, it is frequently subject to misunderstanding and oversimplification. Given its enduring relevance, the prevalence of a superficial grasp of its current structure, and the likelihood that the latest edition will be the final one, this paper seeks to achieve the following two objectives: a) clarify the current theoretical framework of principlism, demonstrating its ability to address most criticisms effectively; b) spotlight unresolved theoretical flaws and delve into their philosophical underpinnings. I will then conclude by suggesting a research direction for overcoming these persistent issues.